Digital Inequality and Social Mobility in Southeast Asia: A Policy-Oriented Analysis Based on World Bank and ITU Reports - Tarma Tarma; Nahri Idris; Sunusi Dauda (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation across Southeast Asia has expanded connectivity yet produced uneven social outcomes, raising concerns about whether technological progress enhances or constrains social mobility. Persistent disparities in access, digital capability, and governance coordination suggest that infrastructure growth alone cannot ensure equitable participation in emerging digital economies. This study investigates how digital inequality shapes mobility trajectories through a policy-oriented, non-empirical design grounded in secondary analysis of macro-level indicators and institutional reports from international development agencies. The analytical framework integrates multidimensional digital divide theory with comparative policy interpretation to examine interactions between access, capability formation, and governance regimes across ASEAN contexts. The findings indicate that digital inequality functions as a structural filter rather than a temporary developmental gap. Connectivity expansion tends to reproduce existing socio-economic hierarchies when not accompanied by investment in digital education, workforce adaptation, and inclusive governance. Digital capability emerges as the key mediator linking technological access to upward mobility, while coordinated policy environments strengthen the diffusion of opportunity across social groups. The study concludes that effective digital transformation requires integrated strategies combining infrastructure, skills development, and participatory governance to align technological progress with equitable social advancement in Southeast Asia.